Implementation of Teams Games Tournament to Improve Student’s Learning Activity and Learning Outcome: Classroom Action Research - Wahyu Lestari; Ani Widayati (AL-ISHLAH: Jurnal Pendidikan, 2022)
This research purpose to improve the quality of accounting learning in certain aspects of learning activity and learning outcome through the implementation of the Teams Games Tournament (TGT) learning model. The design of Classroom Action Research (CAR) was used in this study. The research is organized into two cycles, where each cycle includes four important phases in CAR including: planning, action, observation, and reflection/evaluation. The data collection technique uses observations on seven indicators of learning activity and uses pre-test post-test questions to determine an increase in student performance. The results of the study show that the Teams Games Tournament (TGT) model can improve the learning activity and learning outcomes of students in accounting subjects. The average score for student learning activities increased from 71.28% in cycle I to 90.03% in cycle II. The average academic performance in accounting increased from 81.56 on the first cycle test to 95.70 on the second cycle test. This study provides suggestions and recommendations for teachers to use the Teams Games Tournament (TGT) model, as this model can improve the quality of classroom learning, especially in aspects of learning activity and student learning outcomes.